KINERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU DALAM MENCEGAH BANJIR PADA TAHUN 2022 - Hampratama, Ahlunazaril; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Floods in Pekanbaru City have become a "regular" disaster that often occurs throughout the year. In 2022, Pekanbaru City will be recorded as having 363 flood problem points spread throughout the Pekanbaru City area. This is of course still a major problem that the Pekanbaru City government has not been able to resolve. In this research, to conduct an analysis of the Pekanbaru City government regarding its handling of flooding, Performance Theory was used to assess the extent to which the Pekanbaru City government has worked to prevent flooding. The research method used is a qualitative method by explaining descriptively. The type of research data used is primary data in the form of data obtained from research informants as well as secondary data obtained from related documents that can support data for research. The research location was carried out at the Pekanbaru City Public Works and Spatial Planning Department. The results of the research show that the performance of the Pekanbaru City Public Works and Spatial Planning Department in the productivity aspect can be said to be good by showing positive results. In terms of service quality, it is in accordance with what the community needs and wants. In the aspect of responsiveness, responsiveness to community reports/complaints related to flooding, responsiveness to complaints about the IPAL project, and responsiveness in fulfilling community aspirations and hopes are still not good. In the aspect of responsibility, there are still problems with drainage which is experiencing problems but is slow to make improvements and there are still many drainages that are not connected between one area and another. In the aspect of accountability, the relevant public officials have done well, but accountability to the community is still lacking so that the public still feels that the Public Works and Spatial Planning Department has not been optimal in carrying out its duties. Keywords: Performance, Floods, Pekanbaru City PUPR Department